The impact of reverse abdominal breathing on lower limb muscle strength and muscle synergy characteristics in Tai Chi Chuan - Yin, Yanyu; Zhang, Yanlong; Wang, Minghui; Zhu, Yuhang; Bi, Gengchao; Zhang, Shuo (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveTo investigate the impact of two different breathing methods on lower limb muscle strength and muscle synergy in Tai Chi Chuan, and to reveal the joint control strategies of posture stability and synergy associated with the reverse abdominal breathing in Tai Chi Chuan.MethodsFifteen subjects aged between 33 and 43 years with over 5 years of Tai Chi Chuan experience were selected. High-speed motion capture, a three-dimensional force platform, and surface electromyography were used to collect kinematic and kinetic parameters of Tai Chi Chuan movements under natural breathing and reverse abdominal breathing conditions. Lower limb muscle dynamics were analyzed through computational modeling, and neuromuscular coordination patterns were investigated using muscle synergy analysis techniques. Paired-sample t-tests were used to analyze the differences in various parameters between the two breathing conditions, with significance at P < 0.05.ResultsThe peak muscle strength of the gluteus maximus, rectus femoris, and biceps femoris was consistently greater during reverse abdominal versus natural breathing (P < 0.05), as was tibialis anterior co-activation (P < 0.05). Conversely, lateral gastrocnemius-tibialis anterior co-activation patterns showed distinctly lower values (P < 0.05). The stiffness of the knee and ankle joints significantly increased (P < 0.05). In terms of muscle synergy, in the synergy units dominated by the gluteus maximus, rectus femoris, and semitendinosus, the relative weight during reverse abdominal breathing was significantly higher than that during natural breathing (P < 0.05), exhibiting a more efficient muscle synergy.ConclusionReverse abdominal breathing in Tai Chi Chuan enhances muscle activation and synergy, which facilitates increased recruitment of lower limb muscles and optimize joint strategies, thereby improving the stability and coordination of posture control. Reverse abdominal breathing optimized the activation pattern of lower limb muscles, playing an important role in enhancing stability and coordination in individuals with over 5 years of Tai Chi Chuan experience, particularly in the contexts of physical fitness and sports rehabilitation.